Revitalisasi Budaya Gotong Royong Untuk Pengelolaan Sampah Berkelanjutan Di Kelurahan Sawah Lebar Kota Bengkulu - Malasari, Tara; Dwiyanti, Natasya; Ilmi, Ilma Adhyka Farizky; Ardinata, Bayu; Caniago, Aldo; Moulina, Methatias Ayu; Sumantri, Ajis; Yulianti, Liza (LPPM Universitas Dehasen Bengkulu, 2026)
Gotong royong is a noble tradition of Indonesian nation that has experienced degradation in modern era, especially in urban areas. This study examines the revitalization of gotong royong culture as a sustainable waste management strategy in RT 28 RW 07 Sawah Lebar Village Bengkulu City. Main problems include low community participation in collective activities, minimal waste sorting awareness, and lack of environmental education media. Implementation methods include Focus Group Discussion, scheduled mutual cooperation, installation of visual education media, waste sorting training, Results show an increase in community participation up to 75%, installation of Waste decomposition period education signs, implementation of mandatory reporting system for boarding house residents. This program successfully builds community collective awareness in maintaining environmental cleanliness by utilizing local wisdom of gotong royong.